ASSESSMENT OF COMMUNITY PARTICIPATION IN PRIVATISED DOMESTIC SOLID WASTE MANAGEMENT IN TANZANIA: A CASE OF KINONDONI MUNICIPAL RESIDENTS - Kibonde, Suma Fahamu (European Scientific Journal, ESJ, 2014)
This study aimed at assessing the extent of participation of the Kinondoni Municipal residents in the privatised domestic solid waste management. The study was centred in few selected wards of Kinondoni Municipality which are; Mabibo, Ndugumbi and Sinza. These three wards were represented by three streets which included Jitegemee, Mikoroshini and Sinza “B”. Questionnaires, interviews and physical observations were used as tools for data collection. Considering the matter of residents’ participation on the privatisation of domestic solid waste management, the results indicated that the majority of residents in the Municipality participated though involuntarily. The residents in the study area were paying different amounts of cash as refuse collection charges to the private sector agents dealing with waste collection in their streets. It was further observed that the majority of the inhabitants were not complying with the charges due to various reasons such as charges being high, the poor perception that it is the responsibility of the government to provide such a service free of charge. Not only, that but, the residents were not satisfied with the quality of services provided by the private agents especially in waste collection. This study recommended that the recruitment procedures to get private service providers should be reviewed, also municipality leaders should assume their responsibilities of supervising the performance of the private sector agents, and lastly, political will from the local government leaders is highly urged in the whole process of engaging private firms in all aspects of environmental sanitation.